Comparative Analysis of the Effect of Joule Heating and Slip Velocity on Unsteady Squeezing Nanofluid Flow. (16th August 2022) - Ullah, Hakeem; Khan, Hina; Fiza, Mehreen; Ullah, Kashif; Islam, Saeed; Al-Mekhlafi, Seham M.
Abstract : In this paper, we studied unsteady MHD nanofluid squeezing flow between two parallel plates considering the effect of Joule heating and thermal radiation. The governing equations in the form of partial differential equations (PDEs) are transformed into a system of ordinary differential equations (ODEs) with the help of similarity transformation. The obtained boundary value problem is solved analytically by optimal auxiliary function method (OAFM) and numerically by Runge–Kutta method of order 4 (RKMO4). The OAFM results are validated and compared to the results of RKMO4. The effects of physical parameters such as stretching parameter S, Prandtl number Pr, Eckert number Ec, magnetic number M, volume friction φ electric parameter E 1, and porous parameter γ on the velocity, temperature, and concentration profiles are discussed with the help of plots. Also, the skin friction and Nusselt numbers effects are discussed with the help of tabular data. As the plates move apart, the Nusselt number and the skin friction coefficient decline and the Prandtl number decreases the temperature profile, whereas the stretching and Eckert number increases causing to increase the temperature field.